(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The Integral Relationship between the Theory and The Method in the framework of Scientific Social Research This study approaches the relationship between social Theory and the Method, in the framework of the research using analytical descriptive Method in the study , so it handled the contributions of theory and the Method in promoting and developing the scientific social knowledge , and focused on the issue of using the theory in the research , illustrating both viewpoints : the first separates between theory and the Method, while the second views the theory as a theory and the Method at the same time . The importance of the study springs up from the importance of the theory and the Method in enabling the researcher to reach scientific results in the research . The study aimed at recognizing how to form a new theory through changing or modifying methodology procedures during the performance of the research in accordance with the updates of field work , and to recognize the mechanism of the theory and the Method act in the course of the research . The study came out with some results such as: The relationship between the social theory and the Method is reactive and mutual , since the role of each integrates the other , with core distinction in theoretical entrances and the methodological procedures at handling the social phenomena in itself by two researchers of two different trends in sociology , the possibility of transferring the complex conceptual identifications, through forming due perceptual identifications from the conceptual level – theoretically to experimental level – recognized .